Discordance of global assessment between the patients and physicians predicts 9-year pain-related outcomes in rheumatoid arthritis patients - Hayashi, Kazuhiro; Miki, Kenji; Shi, Kenrin; Yukioka, Masao; Hirayama, Takehiro; Tsujimoto, Kohei; Takeuchi, Takao; Hayaishi, Yasuhisa; Hayaishi, Masahiro (Frontiers in Medicine, 2023)
Introduction Perspectives regarding the disease state often differ between patients with rheumatoid arthritis (RA) and physicians. The aim of the present longitudinal cohort study was to investigate the impact of the discordance in global assessments between patients and physicians on 9-year pain-related outcomes in patients with rheumatoid arthritis. Method Sixty-eight consecutive outpatients with rheumatoid arthritis on their first visit to a tertiary center were included. Baseline measurements included demographic data, drugs used, disease activity, and a modified Health Assessment Questionnaire (mHAQ). Discordance in global assessment between patients and physicians at baseline was defined as 10 mm higher in the patient global assessment (PGA) than in the physician global assessment. A 9-year follow-up assessment included pain intensity, the European Quality of Life 5 Dimensions 3 Level (EQ-5D-3L) scale, Pain Catastrophizing Scale (PCS), Hospital Anxiety and Depression Scale (HADS), Pain Disability Assessment Scale (PDAS), and Pain Self-Efficacy Questionnaire (PSEQ). Results The number of patients with discordance was 26 (38%) in 68 patients. Patients with a 10 mm higher PGA than the physician global assessment at baseline measurements had significantly worse pain intensity, PCS score, PSEQ score, and EQ-5D-3L score measurements at the 9-year follow-up than those with concordance. A higher mHAQ score and 10 mm higher PGA at baseline were significantly independently associated with the EQ-5D-3L scale score and pain intensity at the 9-year follow-up. Conclusion This longitudinal cohort study suggested that discordance in global assessment between patients and physicians modestly predicted worse 9-year pain-related outcomes in patients with rheumatoid arthritis.